Stenting versus gastrojejunostomy for management of malignant gastric outlet obstruction: comparison of clinical outcomes and costs - Roy, Ann (Springer-Verlag, 2012)
BACKGROUND: Although endoscopic stenting is increasingly performed, surgical gastrojejunostomy (GJ) is still considered the gold standard for relief of malignant gastric outlet obstruction (GOO). The aim of this study is to compare clinical outcomes and hospital costs between patients undergoing GJ or stenting for management of malignant GOO. METHODS: A retrospective claims analysis of the Medicare (MedPAR) database was conducted to identify all inpatient hospitalizations for GJ or endoscopic stenting for malignant GOO during 2007–2008. The main outcome measure evaluated using the MedPAR database was a comparison of the total length of hospital stay (LOS) and costs associated with both techniques. As MedPAR is a claims database that does not provide outcomes at patient level, a single-institution retrospective study was conducted to compare the rates of technical and treatment success, post-procedure LOS, and delayed complications per patient between the two techniques. RESULTS: The MedPAR claims data evaluated 425 stenting and 339 GJ hospitalizations. Compared with GJ, median LOS (8 vs. 16 days; p < 0.0001) and median cost (US $15,366 vs. US $27,391; p < 0.0001) per claim were both significantly lower for stenting. Stenting was more commonly performed at urban versus rural hospitals (89 % vs. 11 %; p < 0.0001), teaching versus non-teaching hospitals (59 % vs. 41 %, p = 0.0005), and academic institutions (56 % vs. 44 %; p = 0.0157). The institutional patient data analysis included 29 patients who underwent stenting and 75 who underwent surgical GJ. While both modalities were technically successful and relieved gastric outlet obstruction in all cases, compared with surgical GJ, the median post-procedure LOS was significantly lower for enteral stenting (1.5 vs. 10.7 days, p < 0.0001). There was no difference in rates of delayed complications between stenting and surgical GJ (13.8 % vs. 6.7 %; p = 0.26). CONCLUSIONS: While the technical and clinical outcomes of surgical GJ and endoscopic stenting appear comparable, stent placement is less costly and is associated with shorter length of hospital stay. Dissemination of endoscopic stenting beyond teaching, academic hospitals located in urban areas as a treatment for malignant GOO is important given its implications for patient care and resource utilization.